Diabetes duration-specific association of dietary inflammatory index with the risk of mortality among individuals with diabetes - Xi Chen; Lixia Lin; Yuhe Tan; Ya Zhu; Wuxing Song; Hao Wang; Xufang Sun (Diabetology & Metabolic Syndrome, 2025)
Abstract Background The dietary inflammatory index (DII) is a literature-derived index to assess the inflammatory potential of diet. While numerous studies have linked a higher DII score to an increased risk of mortality, there are limited studies among individuals with diabetes. Objective To investigate the association of the DII with all-cause mortality, cardiovascular disease (CVD) mortality, and cancer mortality among individuals with diabetes, and to explore whether diabetes duration could modify these associations. Methods A total of 9942 participants with diabetes from the UK Biobank were included. The DII scores were calculated based on 24-h dietary data. Outcomes were ascertained from linked records. The hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality according to DII quartiles were estimated using Cox proportional hazards models. Results During the median follow-up period of 12.1 years, 1225 (12.3%) participants with diabetes died. The multivariable HRs (95% CIs) in the highest quartile compared with the lowest DII quartiles were 1.30 (1.06, 1.58) for mortality, 1.67 (1.13, 2.48) for CVD mortality, and 1.00 (0.73, 1.38) for cancer mortality. Spline regression analysis indicated significant nonlinear associations between DII and mortality, while the relationship with CVD mortality was linear. Moreover, diabetes duration significantly modified the association between DII and all-cause mortality (P-interaction = 0.002). In participants with diabetes duration of less than 5 years, the HR (95% CIs) for all-cause mortality in the highest versus lowest DII quartile was 1.73 (1.25, 2.39), while for those with diabetes duration of 5 years or more, the HR (95% CIs) was 1.08 (0.83, 1.39). Conclusion A higher DII, indicating a pro-inflammation dietary pattern, is associated with an elevated risk of all-cause mortality and CVD mortality in individuals with diabetes. Notably, the association with mortality is more pronounced in those with diabetes duration less than 5 years.